Nitride semiconductor light emitting element and method for manufacturing nitride semiconductor light emitting element
Patent Information
- Application Number
- JP2022066965
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-14
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-04-14
AI Technical Summary
Existing nitride semiconductor multilayer reflectors suffer from high defect densities and poor conductivity due to threading dislocations, particularly in structures involving AlInN and GaN layers, which affect the performance and longevity of nitride semiconductor light emitting devices.
A nitride semiconductor light emitting device with a specific layer structure and manufacturing method, including a first layer of AlInN, a GaN cap layer, and an n-AlGaN compositionally graded layer with a controlled AlN mole fraction and thickness, combined with controlled growth temperatures to reduce defects and enhance conductivity.
The proposed structure results in a nitride semiconductor light emitting device with low pit density, good conductivity, and improved electron exchange, leading to enhanced device performance and longevity.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a nitride semiconductor light-emitting device and a method for manufacturing a nitride semiconductor light-emitting device. [Background technology]
[0002] When manufacturing semiconductor multilayer films by stacking nitride semiconductor thin films with different band gaps and refractive indices, a problem has arisen, particularly in multilayer reflecting mirrors made of nitride semiconductor thin films containing in (In), where defects such as through-dislocations are present at high density. Specifically, there is concern about the occurrence of defects in heterojunctions where an in-free nitride semiconductor thin film, such as GaN, is formed on an in-containing nitride semiconductor thin film, such as AlInN.
[0003] Patent Document 1 discloses a method to suppress the occurrence of defects such as through dislocations by creating a structure in which the rate at which the In composition decreases at the interface between the upper part of the AlInN layer and the lower part of the GaN layer decreases is greater than the rate at which the Al composition decreases, that is, a layer with substantially less In exists at the interface between the AlInN layer and the GaN layer. Specifically, it discloses a method to suppress the occurrence of defects by forming an In-free cap layer greater than 0 nm and less than or equal to 1 nm immediately after forming the AlInN layer, and then performing a heating step to raise the substrate temperature, thereby removing In clusters present on the surface of the AlInN layer. Here, the cap layer includes not only a state in which the surface of the AlInN layer is evenly covered, but also a state in which it is formed in an island-like manner on the surface of the AlInN layer. Furthermore, Patent Document 2 discloses a method to increase the reflectivity by increasing the effective refractive index step by providing an AlGaN layer of several nm on the cap layer with an Al composition (AlN mole fraction) of less than 20% (0.2). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2018-98347 [Patent Document 2] Japanese Patent Publication No. 2018-98340 [Non-Patent Document 1] :Schulz, et al., "Composition dependent band gap and band edge bowing in AlInN: A combined theoretical and experimental study"Appl. Phys. Express 6, 121001 (2013) [Non-Patent Document 2] :Coughlan, et al., "Band gap bowing and optical polarization switching in Al1-xGaxN alloys"Phys. Stat. Sol. B 252,879 (2015) [Non-Patent Document 3] :Bernardini, et al., "Spontaneous polarization and piezoelectric constants of III-V nitrides"Phys. Rev. B 56, R10024 (1997) [Overview of the project] [Problems that the invention aims to solve]
[0005] Under these circumstances, in order to form a device structure, a conductive nitride semiconductor thin-film multilayer reflector structure that is advantageous from the viewpoint of current injection was investigated, and the following new challenges were found. Specifically, this is the case when a conductive multilayer reflector structure is formed by providing an n-AlGaInN composition gradient layer with Si added on an n-AlInN layer. First, a 5 nm n-AlGaInN composition gradient layer, that is, a layer in which the composition is gradually changed from n-AlInN to n-GaN, was formed on the n-AlInN layer at the same growth temperature as the n-AlInN layer so that the necessary In is included. After that, a 0.3 nm GaN cap layer was formed according to Patent Document 1, and then a heating step was performed to raise the substrate temperature.
[0006] Although the multilayer mirrors fabricated using this process showed good conductivity, it was found that they produced more pits (holes) on the surface compared to non-conductive multilayer mirrors without using an n-AlGaInN composition gradient. This is thought to be because, since the n-AlGaInN composition gradient layer is formed at the same temperature as the n-AlInN layer (i.e., a lower temperature) to a thickness of 5 nm, a GaN layer equivalent to 1 nm or more in thickness is substantially present on the surface, reducing the effect of reducing pits and through-dislocations. On the other hand, even when an n-AlGaN layer with an AlN mole fraction of 20% (0.2) or less was provided according to Patent Document 2, and Si, an n-type impurity, was added, good conductivity could not be obtained. Thus, it became clear that the techniques disclosed in Patent Documents 1 and 2 alone are insufficient to obtain a multilayer mirror with suppressed dislocation generation and good conductivity.
[0007] The present invention has been made in view of the above-mentioned conventional circumstances, and aims to provide a high-power and long-life nitride semiconductor light-emitting element, and a method for manufacturing a nitride semiconductor light-emitting element, by obtaining a multilayer reflecting mirror with a low surface pit density, i.e., few defects, and good conductivity. [Means for solving the problem]
[0008] The nitride semiconductor light-emitting device of the first invention is A first layer containing Al and In in its composition, A cap layer containing Ga is laminated on the surface of the first layer, A second layer is laminated on the surface of the aforementioned cap layer and contains Al and Ga in its composition, Equipped with, The mole fraction of AlN at the interface of the second layer laminated on the surface of the cap layer is 0.36 or more and 0.44 or less.
[0009] This configuration reduces the energy barrier between the first and second layers, and improves the exchange of electrons between the first and second layers.
[0010] The method for manufacturing a nitride semiconductor light-emitting element according to the second invention is: A method for manufacturing a nitride semiconductor light-emitting device using metalorganic vapor phase epitaxy, comprising: a first layer stacking step of growing a first layer containing Al and In in its composition; a cap layer stacking step of growing a cap layer containing Ga in its composition on the surface of the first layer after performing the first layer stacking step; a second layer stacking step of growing a second layer containing Al and Ga in its composition on the surface of the cap layer after performing the cap layer stacking step; a third layer stacking step of growing a third layer containing Ga in its composition on the surface of the second layer after performing the second layer stacking step; wherein the temperature for growing the second layer in the second layer stacking step is equal to or higher than the temperature for growing the third layer in the third layer stacking step.
[0011] According to this configuration, migration of Al can be activated in the second layer stacking step, so that the surface of the second layer can be easily flattened, leading to an improvement in the quality of the third layer that grows crystallographically thereafter.
Brief Description of the Drawings
[0012] <(A) is a schematic diagram showing the structure of the samples from Examples 1 to 4 and Comparative Examples 1 and 2, and (B) is a table showing the initial AlN mole fraction, growth temperature, and differential resistance value for Examples 1 to 4 and Comparative Examples 1 and 2. [Figure 6] This graph shows the relationship between voltage and current in the samples of Examples 1 to 4 and Comparative Examples 1 and 2. [Figure 7] This graph plots the relationship between the starting AlN mole fraction and the differential resistance value for the samples in Examples 1 to 4 and Comparative Example 1. [Figure 8] This graph plots the differential resistance values at multiple points in each of the samples from Examples 1 to 4 and Comparative Example 1. [Figure 9] This graph shows the relationship between maximum reflectivity and the thickness of n-AlGaN composition gradient layers. [Figure 10] This graph shows the relationship between the energy barrier at the interface between the n-AlInN layer and the n-AlGaN composition gradient layer, and the thickness of the n-AlGaN composition gradient layer. [Figure 11] These are AFM images of each surface of Example 5 and Comparative Examples 3 and 4, measured over a 10 μm × 10 μm area. [Modes for carrying out the invention]
[0013] Preferred embodiments of the present invention will be described.
[0014] In the first invention, a third layer is further laminated on the surface of the second layer, the mole fraction of AlN is smaller than that of the first layer, and the composition contains Ga. The mole fraction of AlN in the second layer can be graded so that it gradually decreases towards the interface with the third layer. With this configuration, the energy barrier generated at the interface between the second and third layers can be kept small, thereby improving the conductivity between the second and third layers, and thus improving the exchange of electrons between the first to third layers (i.e., improving conductivity).
[0015] In the first invention, the thickness of the cap layer in the stacking direction may be greater than 0 and less than or equal to 1 nm. This configuration allows for good protection of the surface of the first layer.
[0016] In the first invention, the thickness of the second layer in the stacking direction may be 4 nm or more and 15 nm or less. This configuration makes it possible to achieve both low differential resistivity and high reflectivity.
[0017] <Examples 1-4, Comparative Examples 1-2> Next, an example of embodying the nitride semiconductor light-emitting element of the present invention will be described with reference to the drawings. Specifically, this is an example of forming an n-AlInN / GaN multilayer reflector structure having an n-AlGaN composition gradient layer 14 on the surface side of an n-AlInN layer 12, and a method for manufacturing a surface-emitting laser (hereinafter also referred to as nitride semiconductor light-emitting element 1) using this structure. The n-AlInN / GaN multilayer reflector structure can be used not only in surface-emitting lasers but also in various optical device structures such as light-emitting diodes and solar cells. A schematic cross-sectional view of an example of the structure of a surface-emitting laser (nitride semiconductor light-emitting element 1) using this structure is shown in Figure 1.
[0018] As shown in Figure 1, the nitride semiconductor light-emitting element 1 comprises an n-GaN substrate 10, an n-GaN buffer layer 11, an n-AlInN / GaN multilayer reflector M, a second n-GaN layer 16, a GaInN quantum well active layer 17, a p-AlGaN layer 18, a p-GaN layer 19, a p-GaN contact layer 20, a p-side electrode 22A, and an n-side electrode 22B. The n-AlInN / GaN multilayer reflector M is formed by repeating four layers 40 times: a first n-AlInN layer 12, a cap layer GaN cap layer 13, a second n-AlGaN composition gradient layer 14, and a third first n-GaN layer 15. The n-GaN substrate 10 is a single crystal substrate of GaN having n-type properties. The nitride semiconductor light-emitting element 1 can be manufactured by performing epitaxial growth on the surface of the n-GaN substrate 10, i.e., the Ga surface (the upper surface in Figure 1), using metal-organic vapor phase epitaxy (MOVPE).
[0019] When manufacturing nitride semiconductor light-emitting element 1, TMA (trimethylaluminum), TMGa (trimethylgallium), TEGa (triethylgallium), and TMI (trimethylindium) are used as Group III materials (MO raw materials). Ammonia (NH3) is used as the raw material gas for Group V materials. SiH4 (silane) is used as the raw material gas for donor impurities. CP2Mg (cyclopentadienylmagnesium) is used as the MO raw material for acceptor impurities.
[0020] First, an n-GaN buffer layer 11 is grown on the surface of the n-GaN substrate 10 as a buffer layer. The thickness of the n-GaN buffer layer 11 in the stacking direction is 500 nm. Here, the stacking direction is the vertical direction in Figure 1. Hereafter, the thickness in the stacking direction will also be simply referred to as thickness. Specifically, the n-GaN substrate 10 is placed inside the reaction furnace of the MOVPE apparatus (hereinafter also simply referred to as the reaction furnace). Then, the temperature inside the reaction furnace is adjusted so that the temperature of the n-GaN substrate 10 (growth temperature) is 1050°C, and H2 (hydrogen) is supplied into the reaction furnace as a carrier gas. The concentration of Si (silicon) in the n-GaN buffer layer 11 is 5 × 10⁻¹⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.
[0021] [First layer lamination process] Next, the first layer lamination process is performed. Specifically, an n-AlInN layer 12 containing Al and In in its composition is epitaxially grown on the surface of the n-GaN buffer layer 11. More specifically, the temperature inside the reactor is adjusted so that the temperature of the n-GaN substrate 10 (growth temperature) is 840°C, and N2 (nitrogen) is supplied to the reactor as a carrier gas. In addition, TMA, TMI, SiH4, and NH3 are supplied to the reactor to crystallize an n-AlInN layer 12 with a thickness of 38 nm in the lamination direction. The mole fraction of AlN in the n-AlInN layer 12 is approximately 81% (0.81), and the mole fraction of InN is approximately 19% (0.19).
[0022] Basically, it is preferable to match the lattice constant of the n-AlGaN composition gradient layer 14, described later, to the lattice constant of the n-GaN substrate 10, which is the substrate. However, in this embodiment, the lattice constant of the n-AlGaN composition gradient layer 14 is set to be smaller than the lattice constant of the n-GaN substrate 10. To compensate for this, the mole fraction of InN in the n-AlInN layer 12 is slightly increased (less than 1% (0.01)) to approximately 19% (0.19). This cancels out the cumulative lattice strain of the entire multilayer mirror structure. Note that the mole fractions of AlN and InN in the n-AlInN layer 12 are not limited to the values disclosed in this embodiment, but may be any value that can cancel out the cumulative lattice strain of the entire multilayer mirror structure. The Si concentration in the n-AlInN layer 12 is 1.5 × 10⁻⁶. 19 cm -3 The amount of SiH4 supplied to the reactor is adjusted so that the desired result is achieved. The carrier gas may be an inert gas other than N2, such as Ar or Ne (neon), or a mixed gas of these.
[0023] [Cap layer lamination process] Next, after the first layer lamination process is performed, the cap layer lamination process is carried out. Specifically, while maintaining the temperature (growth temperature) of the n-GaN substrate 10, the carrier gas (N2), and the supply of NH3 to the reactor, the supply of TMA, TMI, and SiH4 is stopped, and TEGa is supplied to the reactor to crystallize the GaN cap layer 13 on the surface of the n-AlInN layer 12. The GaN cap layer 13 contains Ga in its composition. The thickness of the GaN cap layer 13 in the lamination direction is 0.6 nm. If the thickness of the GaN cap layer 13 is less than 1 nm, there is no significant effect even if SiH4 is not added, but SiH4 may be supplied. If SiH4 is supplied, the Si concentration should be 5 × 10⁻⁶ 18 cm -3 Adjust to achieve the desired degree.
[0024] Furthermore, as described below, it is preferable to adjust the thickness of the GaN cap layer 13 according to the substrate temperature during crystal growth in the step following the cap layer lamination process. For example, if the substrate temperature during crystal growth in the step following the cap layer lamination process is higher than the substrate temperature in the cap layer lamination process, the thickness of the GaN cap layer 13 should be increased. This reduces damage to the surface of the n-AlInN layer 12 due to the high substrate temperature in the next step and allows for a flatter surface formation of the n-AlInN layer 12. Specifically, if the substrate temperature in the next step is around 1050°C, the thickness of the GaN cap layer 13 is preferably 0.3 nm to 0.6 nm. Also, if the substrate temperature in the next step is 1100°C or higher, the thickness of the GaN cap layer 13 is preferably 0.6 nm to 1 nm. In other words, regardless of the substrate temperature, the thickness of the GaN cap layer 13 in the lamination direction should be greater than 0 and 1 nm or less.
[0025] [Heating process] Next, a heating step is performed. Specifically, after stopping the supply of TEGa, while maintaining the supply of NH3 into the reactor, the temperature (growth temperature) of the n-GaN substrate 10 is raised to 1100°C, which is the growth temperature of the n-AlGaN composition gradient layer 14, while gradually switching the carrier gas supplied to the reactor from N2 to H2. At this time, since the supply of TMA, TMGa, TEGa, TMI, and SiH4 into the reactor is stopped, crystal growth is interrupted. In this way, after forming a thin GaN cap layer 13 that does not contain In, a heating step is performed to raise the temperature of the n-GaN substrate 10 on the surface of the GaN cap layer 13. This makes it possible to remove In clusters present on the surface of the n-AlInN layer 12 and suppress the occurrence of defects, as disclosed in Patent Document 1. However, in the next step, since the n-AlGaN composition gradient layer 14, which contains Al with a high binding energy, is to be crystallized, it is necessary to activate the migration of Al on the surface of the substrate. Therefore, by setting the growth temperature in the second layer stacking process to be higher than the growth temperature of the first n-GaN layer 15 stacked on the surface of the n-AlGaN composition gradient layer 14, a flatter surface of the n-AlGaN composition gradient layer 14 can be obtained.
[0026] [Second layer lamination process] Next, the second layer lamination process is performed. Specifically, after the temperature of the n-GaN substrate 10 reaches 1100°C, the supply of TMGa, TMAl, and SiH4 into the reaction furnace is started, and an n-AlGaN composition gradient layer 14 containing Al and Ga but not In is grown. The thickness of the n-AlGaN composition gradient layer 14 in the lamination direction is 5 nm. The n-AlGaN composition gradient layer 14 is laminated on the surface of the GaN cap layer 13. The n-AlGaN composition gradient layer 14 is grown in the following manner.
[0027] First, crystal growth is started with predetermined supply amounts of TMA and TMGa. By changing the ratio of TMA and TMGa supply amounts, the mole fraction of AlN at the start of crystal growth of the n-AlGaN composition gradient layer 14 (hereinafter also simply referred to as the starting AlN mole fraction) can be adjusted. Immediately after the start of crystal growth of the n-AlGaN composition gradient layer 14, the supply amount of TMA into the reactor is gradually decreased, while the supply amount of TMGa is gradually increased. Finally, the supply of TMA into the reactor is completely stopped, and the supply amount of TMGa is increased to a level that results in a growth rate similar to that at the start of growth of the n-AlGaN composition gradient layer 14. This allows for the crystal growth of an n-AlGaN composition gradient layer 14 that is n-AlGaN when crystal growth starts in the stacking direction, and changes in composition as it gradients towards n-GaN when crystal growth ends. In other words, the mole fraction of AlN in the n-AlGaN composition gradient layer 14 is graded so that it gradually decreases as it approaches the interface with the first n-GaN layer 15, which will be described later. The thickness of the n-AlGaN composition gradient layer 14 is 5 nm. While there is a preferred thickness for the n-AlGaN composition gradient layer 14, this will be discussed later. Furthermore, in order to obtain n-type properties, the Si concentration in the n-AlGaN composition gradient layer 14 is 6 × 10⁻⁶. 19 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.
[0028] After the supply of TMGa and SiH4 is stopped and the growth of the n-AlGaN composition gradient layer 14 is completed, the temperature of the n-GaN substrate 10 is lowered to 1050°C, which is the appropriate temperature for the crystal growth of the next first n-GaN layer 15. In other words, the temperature at which the n-AlGaN composition gradient layer 14 is crystal grown in the second layer stacking process (1100°C) is higher than the temperature at which the first n-GaN layer 15 is crystal grown in the third layer stacking process that is subsequently performed (1050°C).
[0029] [Third layer lamination process] Next, after performing the second layer stacking process, the third layer stacking process is performed. Specifically, after the temperature of the n-GaN substrate 10 reaches 1050 °C, the supply of TMGa into the reaction furnace is started, and the first n-GaN layer 15 having a thickness of 43 nm in the stacking direction and containing Ga in its composition is grown crystallographically. The molar fraction of AlN in the first n-GaN layer 15 is 0 (i.e., smaller than that of the n-AlInN layer 12). The concentration of Si in the first n-GaN layer 15 is adjusted to 5×10 18 cm -3 by adjusting the supply amount of SiH4 into the reaction furnace. The n-AlInN layer 12, the GaN cap layer 13, the n-AlGaN composition gradient layer 14, and the first n-GaN layer 15 correspond to one pair P of the multilayer mirror structure.
[0030] After growing the first n-GaN layer 15 crystallographically, the supply of TMGa into the reaction furnace is stopped to interrupt the crystal growth in order to grow the n-AlInN layer 12 crystallographically again on the surface of the first n-GaN layer 15 (i.e., to repeatedly grow the pair P crystallographically). Then, while the crystal growth is interrupted, the temperature of the n-GaN substrate 10 is decreased from 1050 °C to 840 °C. At this time, the carrier gas is gradually switched from H2 to N2. Thus, an n-AlInN / GaN multilayer mirror M in which 40 pairs P of the multilayer mirror structure (the n-AlInN layer 12, the GaN cap layer 13, the n-AlGaN composition gradient layer 14, and the first n-GaN layer 15) are stacked is grown crystallographically by repeatedly growing one pair P of the multilayer mirror structure 40 times.
[0031] [Verification of the starting AlN molar fraction of the AlGaN composition gradient layer] Here, the nitride semiconductor light-emitting device 1 uses the n-AlInN layer 12 and the n-AlGaN composition gradient layer 14. Therefore, the connection of the band structure at the heterointerface formed by the upper part of the n-AlInN layer 12 and the lower part of the n-AlGaN composition gradient layer 14 (i.e., the n-AlGaN composition gradient layer 14 at the start of growth) via the GaN cap layer 13 has a great influence on the conductivity of the multilayer structure.
[0032] In other words, in layers with n-type conductivity, such as the n-AlInN layer 12 and the n-AlGaN composition gradient layer 14, electrons move, so it is extremely important to select a starting AlN mole fraction that does not create an unnecessary barrier in the energy levels at the heterointerface at the lower end of the conduction band. Incidentally, if an AlGaInN composition gradient layer is used instead of the n-AlGaN composition gradient layer 14, in which the mole fractions of AlN, GaN, and InN are continuously changed along with crystal growth to match the composition of the first n-GaN layer 15 from the composition of the n-AlInN layer 12, the band gap changes continuously from the n-AlInN layer 12 to the first n-GaN layer 15, and therefore the above-mentioned problems do not occur.
[0033] To determine the initial AlN mole fraction that does not create an unnecessary barrier in the energy levels at the heterointerface at the lower end of the conduction band, it is important to consider both the band offset of the conduction band based on the difference in band gaps between the AlInN layer and the AlGaN layer, and the polarization charge offset based on the difference in polarization charge. Specifically, it is thought that there exist AlN mole fractions such that both the band offset of the conduction band based on the difference in band gaps between the AlInN layer and the AlGaN layer, and the polarization charge offset based on the difference in polarization charge, are zero.
[0034] Here, using the physical properties disclosed in Non-Patent Documents 1 and 2, we calculated the AlN mole fraction of AlGaN that coincides with the lower end of the conduction band of the n-AlInN layer 12 (AlN mole fraction of 0.81) used in the n-AlInN / GaN multilayer mirror M, and found that the value was 0.25 (see Figure 2). On the other hand, using the physical properties disclosed in Non-Patent Document 3, we calculated the AlN mole fraction of AlGaN that coincides with the polarization charge at the top of the n-AlInN layer 12 and has a zero offset, and found that the value was 0.45 (see Figure 3).
[0035] Based on these two physical properties, the potential barrier generated at the bottom of the conduction band was simulated. As shown in Figure 4, the results showed that the potential barrier generated at the bottom of the conduction band between the n-AlInN layer 12 and the AlGaN layer was minimized (approximately 0.18 eV) when the initial AlN mole fraction of the AlGaN layer stacked on the n-AlInN layer 12 was set to 0.27. Furthermore, it was found that the potential barrier increased when the initial AlN mole fraction was less than 0.27, and also increased when the initial AlN mole fraction was greater than 0.27. In other words, Figure 4 suggests that the resistance of the device can be minimized by setting the AlN mole fraction at the start of crystal growth to 0.27 in the n-AlGaN composition gradient layer 14, and that the resistance of the device can increase whether the AlN mole fraction is greater or less than 0.27. Furthermore, Figure 4 shows that when the initial AlN mole fraction is 0.36 or higher, the potential barrier increases monotonically, and the resistance of the device increases accordingly.
[0036] To understand the relationship between the initial AlN mole fraction and the resistance of the n-AlInN / GaN multilayer reflector M, five types of samples were prepared, Examples 1 to 4 and Comparative Example 1, each having a multilayer reflector Mt formed by repeating pair P 10 times, as shown in Figure 5. These samples consist of a sapphire substrate S with a c-plane (0001) surface, on which a u-GaN layer 30 and an n-GaN layer 31 are laminated in that order, and a multilayer reflector Mt is laminated on the surface of the n-GaN layer 31. In one pair P of the multilayer reflector Mt in these samples, an n-AlInN layer 12 (thickness 45 nm), a GaN cap layer 13 (thickness 0.6 nm), an n-AlGaN composition gradient layer 14 (thickness 5 nm), and a first n-GaN layer 15 (thickness 35 nm) are laminated in that order. Furthermore, these samples varied the initial AlN mole fraction to 0.36, 0.39, 0.42, 0.44, and 0.47. The initial AlN mole fraction for each sample was identified from the X-ray diffraction curves of GaN / AlGaN superlattices fabricated separately under the same growth conditions.
[0037] Furthermore, as Comparative Example 2, a sample was also prepared using an n-AlGaInN composition gradient layer 114 (thickness 5 nm) containing many dislocations instead of the GaN cap layer 13 and the n-AlGaN composition gradient layer 14. The n-AlGaInN composition gradient layer 114 has good conductivity because, in principle, the interface with the upper part of the n-AlInN layer 12 and the interface with the lower part of the first n-GaN layer 15 are not heterointerfaces. In each sample, in order to measure the differential resistance value of the multilayer mirror Mt in the longitudinal direction, the multilayer mirror Mt was etched into a mesa shape, and n electrodes E were formed on the surface of the multilayer mirror Mt and on the etched surface around the multilayer mirror Mt, and the current-voltage characteristics in the longitudinal direction were measured.
[0038] Figure 6 shows a graph plotting the best result (smallest differential resistance value) in the current-voltage characteristics of each fabricated sample. Figure 7 shows a graph illustrating the dependence of the differential resistance value on the initial AlN mole fraction, demonstrating the relationship between the initial AlN mole fraction and the differential resistance value. Contrary to the values obtained from simulations using theoretical values (minimum 0.27), the minimum differential resistance value was obtained in the sample with an initial AlN mole fraction of 0.39 (Sample from Example 2). The differential resistance value increased both when the initial AlN mole fraction was greater than or less than 0.39. Furthermore, the differential resistance value of this sample with an initial AlN mole fraction of 0.39 (Sample from Example 2) was almost the same as that of the sample from Comparative Example 2, which used an n-AlGaInN composition gradient layer 114 that exhibited good conductivity because no potential barrier due to band offset was formed at the interface between the n-AlInN layer 12 and the n-AlGaInN composition gradient layer 114.
[0039] Specifically, as shown in Figure 5, the differential resistance of the sample in Example 1 (initial AlN mole fraction 0.36) was 30.6 Ω. The differential resistance of the sample in Example 2 (initial AlN mole fraction 0.39) was 22.3 Ω. The differential resistance of the sample in Example 3 (initial AlN mole fraction 0.42) was 25.6 Ω. The differential resistance of the sample in Example 4 (initial AlN mole fraction 0.44) was 33.7 Ω. The differential resistance of the sample in Comparative Example 1 (initial AlN mole fraction 0.47) was 36.1 Ω. The differential resistance of Comparative Example 2 (sample using n-AlGaInN composition gradient layer 114) was 21.5 Ω. From this, it was found that in the case of an initial AlN mole fraction of 0.39 (Example 2), the effects of band offset and polarization charge offset are minimized, resulting in a low differential resistance value almost equivalent to that of the ideal n-AlGaInN composition gradient layer 114. In other words, it was found that the potential barrier at the lower end of the conduction band is minimized when the initial AlN mole fraction is 0.39 (Example 2).
[0040] Furthermore, Figure 8 shows a graph plotting not only the minimum differential resistance value, but also the results of 32 measurements of differential resistance values by changing the measurement position for each of the five samples from Examples 1 to 4 and Comparative Example 1, as well as the average of these measurement results. In other words, the measurement results shown in Figure 8 include the distribution within the wafer for each sample. Looking at the average differential resistance value for each sample, it was found that the minimum differential resistance value was obtained at an initial AlN mole fraction of 0.39.
[0041] The simulation results shown in Figure 4 suggest that when the initial AlN mole fraction is 0.27 or higher, i.e., 0.36 or higher, the differential resistance increases monotonically with increasing initial AlN mole fraction. On the other hand, the study results shown in Figure 8 show that when the initial AlN mole fraction is greater than 0.36, the differential resistance decreases, reaching a minimum value at an initial AlN mole fraction of 0.39. Furthermore, from an initial AlN mole fraction exceeding 0.39 up to approximately 0.44, the differential resistance remains at a low value, similar to that of 0.36. Finally, it was found that at initial AlN mole fractions of 0.47 or higher, the differential resistance is higher than that of 0.36.
[0042] From the above verification results, it was found that in the range of an initial AlN mole fraction of 0.36 or higher and 0.44 or lower, there exists a low-resistance region where the differential resistance value becomes low, which is unpredictable from the simulation results (theoretical value). By setting the initial AlN mole fraction within this range, it is possible to fabricate a low-resistance n-AlInN / GaN multilayer reflecting mirror M. Furthermore, it was found that even lower-resistance n-AlInN / GaN multilayer reflecting mirror M can be fabricated by setting the initial AlN mole fraction to 0.39 or higher and 0.42 or lower. In other words, it was found that there is an appropriate range of initial AlN mole fraction (0.36 or higher and 0.44 or lower) to reduce the longitudinal differential resistance value of an n-AlInN / GaN multilayer reflecting mirror M in which multiple pairs P are stacked. That is, it is preferable that the AlN mole fraction at the interface of the n-AlGaN composition gradient layer 14 stacked on the surface of the GaN cap layer 13 be 0.36 or higher and 0.44 or lower.
[0043] In this verification, a sample was used in which pair P was repeated 10 times for crystal growth. However, even if the number of stacked pairs P is 11 or more, it is thought that the effect of reducing the longitudinal differential resistance can be achieved by setting the initial AlN mole fraction within this range (0.36 or more and 0.44 or less). In other words, in an n-AlInN / GaN multilayer reflecting mirror M using an n-AlGaN composition gradient layer 14, by setting the initial AlN mole fraction of the n-AlGaN composition gradient layer 14 to a value between 0.36 or more and 0.44 or less, the longitudinal differential resistance of the n-AlInN / GaN multilayer reflecting mirror M with multiple stacked pairs P can be effectively reduced.
[0044] [Regarding the preferred thickness of n-AlGaN composition gradient layers] Increasing the thickness of the n-AlGaN composition gradient layer 14 in the stacking direction reduces the potential barrier and lowers the resistance, while substantially reducing the refractive index step and thus decreasing the reflectivity. Conversely, decreasing the thickness of the n-AlGaN composition gradient layer 14 yields the opposite result. Figure 9 shows the calculation results of the dependence of the maximum reflectivity on the thickness of the n-AlGaN composition gradient layer 14. Figure 10 shows the calculation results of the dependence of the energy barrier (hereinafter simply referred to as the energy barrier) at the interface between the n-AlInN layer 12 and the n-AlGaN composition gradient layer 14 on the thickness of the n-AlGaN composition gradient layer 14. As shown in Figure 9, the thickness of the n-AlGaN composition gradient layer 14 is preferably 15 nm or less, which allows for a reflectivity of 99.9% or more, which is essential for surface-emitting lasers, and where the decrease in reflectivity is gradual.
[0045] On the other hand, as shown in Figure 10, the decrease in the energy barrier is rapid from 0 nm to 4 nm in thickness of the n-AlGaN composition gradient layer 14. However, when the thickness of the n-AlGaN composition gradient layer 14 exceeds 4 nm, the decrease in the energy barrier becomes gradual. Therefore, in order to obtain an n-AlInN / GaN multilayer reflecting mirror M with well suppressed differential resistance, it is preferable to set the thickness of the n-AlGaN composition gradient layer 14 to 4 nm or more. Accordingly, in order to obtain an n-AlInN / GaN multilayer reflecting mirror M that achieves both low differential resistance and high reflectivity, it is preferable to set the thickness of the n-AlGaN composition gradient layer 14 in the stacking direction to 4 nm or more and 15 nm or less. Note that this range of values is considered to be a range in which both low differential resistance and high reflectivity can be achieved in the n-AlInN / GaN multilayer reflecting mirror M, regardless of the magnitude of the starting AlN mole fraction.
[0046] <Example 5, Comparative Examples 3 and 4> [Verification of the surface state of n-AlInN / GaN multilayer reflecting mirrors using n-AlGaN composition gradient layers] Next, we will describe the results of verifying the surface state of the n-AlInN / GaN multilayer reflector M using the n-AlGaN composition gradient layer 14. As Example 5, a sample was prepared by forming 40 pairs of n-AlGaN composition gradient layers 14 on a GaN substrate with an initial AlN mole fraction of 0.39, which yields the lowest differential resistance value. As Comparative Example 3, a sample was prepared by forming 40 pairs of non-conductive multilayer reflectors on a GaN substrate without the n-AlGaN composition gradient layer 14 and without Si doping. As Comparative Example 4, a sample was prepared by forming 40 pairs of conductive multilayer reflectors on a GaN substrate, having an n-AlGaInN composition gradient layer and Si doping. Figure 11 shows AFM images of the surfaces of each sample from Example 5, Comparative Examples 3 and 4 measured over a 10 μm × 10 μm area.
[0047] In Comparative Example 3, no pits were observed on the surface of the sample within a 10 μm × 10 μm measurement range, and the pit density was 1 × 10⁻⁶. 6 cm -2 It is estimated to be less than 1 × 10⁻⁶. On the other hand, on the surface of the sample of Comparative Example 4, 1 × 10⁻⁶ 7 cm -2 A number of pits exceeding 3 × 10 was observed. The pit density on the surface of the sample in Example 5 was 3 × 10 6 cm -2 The result was as low as the pit density of the sample in Comparative Example 3. This means that by using an n-AlGaN composition gradient layer 14 in which the initial AlN mole fraction is 0.36 or higher and 0.44 or lower, it is possible to fabricate an n-AlInN / GaN multilayer reflecting mirror M with good conductivity and crystallinity, i.e., surface flatness. In other words, by setting the initial AlN mole fraction of the n-AlGaN composition gradient layer 14 to 0.36 or higher and 0.44 or lower, it is possible to fabricate an n-AlInN / GaN multilayer reflecting mirror M with good surface flatness.
[0048] Next, we return to the explanation of the fabrication method for the nitride semiconductor light-emitting element 1 shown in Figure 1. After forming an n-AlInN / GaN multilayer reflector mirror M by repeating pair P 40 times to grow crystals, a second n-GaN layer 16 with a thickness of 400 nm is grown on the surface of the n-AlInN / GaN multilayer reflector mirror M at a growth temperature of 1050°C. The Si concentration in the second n-GaN layer 16 is 5 × 10⁻⁶. 18 cm -3 The amount of SiH4 supplied into the reactor is adjusted to achieve this.
[0049] Next, a GaInN quantum well active layer 17 is grown on the surface of the second n-GaN layer 16, consisting of five stacks of a pair of GaInN quantum well layers and a GaN barrier layer. Then, a p-AlGaN layer 18 with a thickness of 20 nm is crystallized on the surface of the GaInN quantum well active layer 17. The mole fraction of AlN in the p-AlGaN layer 18 is 0.2, and the mole fraction of GaN is 0.8. The concentration of Mg in the p-AlGaN layer 18 is 2 × 10⁻⁶. 19 cm -3 Adjust the supply amount of Cp2Mg to achieve this.
[0050] Next, a p-GaN layer 19 with a thickness of 70 nm is grown as a p-type cladding layer on the surface of the p-AlGaN layer 18. The Mg concentration in the p-GaN layer 19 is 2 × 10⁻⁶. 19 cm -3 The supply amount of Cp2Mg is adjusted so that the following occurs. Then, the p-GaN contact layer 20 is grown on the surface of the p-GaN layer 19. The concentration of Mg in the p-GaN contact layer 20 is 2 × 10⁻⁶. 20 cm -3 Adjust the supply amount of Cp2Mg to achieve this.
[0051] Thus, a resonator structure is formed that includes an n-AlInN / GaN multilayer mirror M having an n-AlGaN composition gradient layer 14 with an initial AlN mole fraction of 0.39, where pair P is grown 40 times in a crystal structure, and a GaInN quantum well active layer 17 sandwiched between pn junctions and emitting light in the purple region. This resonator has integer multiples of the emission wavelength, and the resonator length corresponds to 4 wavelengths.
[0052] As shown in Figure 1, a surface-emitting laser is completed by growing an insulating film 21, a p-side electrode 22A, an n-side electrode 22B, and an SiO2 / Nb2O5 dielectric multilayer mirror D on a wafer having an n-AlInN / GaN multilayer mirror M and a resonator structure. The following describes the process of fabricating a surface-emitting laser (nitride semiconductor light-emitting device) by growing the insulating film 21, p-side electrode 22A, n-side electrode 22B, and SiO2 / Nb2O5 dielectric multilayer mirror D.
[0053] First, the p-GaN contact layer 20 is grown in crystal form, then hydrogen is removed from the p-type semiconductor layers (p-AlGaN layer 18, p-GaN layer 19, p-GaN contact layer 20) of the semiconductor wafer, and the Mg, which is a p-type dopant added to the p-type semiconductor layer, is activated. Next, a pattern is formed on the surface of the semiconductor wafer using photoresist, and a mesa structure with a circular shape of 40 μm in diameter is formed by partial etching to create the device.
[0054] Then, a 20 nm thick SiO2 film is laminated onto the surface of the p-GaN contact layer 20, and an insulating film 21 with a circular opening H of 10 μm in diameter is formed by photolithography and sputtering. A transparent p-side electrode 22A made of ITO is then formed by sputtering so as to contact the surface of the p-GaN contact layer 20 exposed through the opening H. At the same time, an n-side electrode 22B is provided on the back surface of the n-GaN substrate 10. A pad electrode made of Cr / Ni / Au is then formed on the outer periphery of the surface of the p-side electrode 22A (not shown).
[0055] Finally, a SiO2 / Nb2O5 dielectric multilayer reflector D is grown on the surface of the p-side electrode 22A using photolithography and sputtering. In this way, a nitride semiconductor light-emitting element is completed that has a vertical cavity surface-emitting laser with a resonator length corresponding to an integer multiple of the wavelength, with a SiO2 / Nb2O5 dielectric multilayer reflector D above the GaInN quantum well active layer 17 and an n-AlInN / GaN multilayer reflector M below it.
[0056] This element features a multilayer reflector with excellent conductivity, crystallinity, and surface flatness, resulting in high uniformity of injected current within the plane and low element resistance, enabling high-efficiency, high-power operation. Furthermore, it has a long element lifespan and high reliability due to the low number of pits and defects.
[0057] Next, the operation in the above embodiment will be explained.
[0058] The nitride semiconductor light-emitting element 1 comprises an n-AlInN layer 12 containing Al and In, a GaN cap layer 13 containing Ga and laminated on the surface of the n-AlInN layer 12, and an n-AlGaN composition gradient layer 14 containing Al and Ga and laminated on the surface of the GaN cap layer 13, wherein the mole fraction of AlN at the interface of the n-AlGaN composition gradient layer 14 laminated on the surface of the GaN cap layer 13 is 0.36 or more and 0.44 or less. This configuration reduces the difference in energy barriers between the n-AlInN layer 12 and the n-AlGaN composition gradient layer 14, and improves electron exchange between the n-AlInN layer 12 and the n-AlGaN composition gradient layer 14.
[0059] The n-AlGaN composition gradient layer 14 is further laminated with a first n-GaN layer 15, which has a smaller mole fraction of AlN than the n-AlInN layer 12 and contains Ga in its composition. The mole fraction of AlN in the n-AlGaN composition gradient layer 14 is graded so that it gradually decreases towards the interface with the first n-GaN layer 15. With this configuration, the energy barrier generated at the interface between the n-AlGaN composition gradient layer 14 and the first n-GaN layer 15 can be kept small, thereby improving the conductivity between the n-AlGaN composition gradient layer 14 and the first n-GaN layer 15. This improves the exchange of electrons between the n-AlInN layer 12 and the first n-GaN layer 15 (i.e., improves conductivity).
[0060] The thickness of the cap layer in the stacking direction is greater than 0 and less than or equal to 1 nm. This configuration allows for good protection of the surface of the n-AlInN layer 12.
[0061] The thickness of the n-AlGaN composition gradient layer 14 in the stacking direction is 4 nm or more and 15 nm or less. This configuration makes it possible to achieve both low differential resistivity and high reflectivity.
[0062] A method for manufacturing a nitride semiconductor light-emitting element is a method for manufacturing a nitride semiconductor light-emitting element using metal-organic vapor phase epitaxy, comprising: a first layer stacking step of growing an n-AlGaN composition gradient layer 14 containing Al and In in its composition; a cap layer stacking step of growing a GaN cap layer 13 containing Ga in its composition on the surface of the n-AlGaN composition gradient layer 14 after the first layer stacking step; a second layer stacking step of growing an n-AlGaN composition gradient layer 14 containing Al and Ga in its composition on the surface of the GaN cap layer 13 after the cap layer stacking step; and a third layer stacking step of growing a first n-GaN layer 15 containing Ga in its composition on the surface of the n-AlGaN composition gradient layer 14 after the second layer stacking step, wherein the temperature at which the n-AlGaN composition gradient layer 14 is grown in the second layer stacking step is higher than the temperature at which the first n-GaN layer 15 is grown in the third layer stacking step. This configuration allows for active Al migration during the second layer stacking process, making it easier to flatten the surface of the n-AlGaN composition gradient layer 14, which in turn leads to improved quality in the first n-GaN layer 15 where crystal growth occurs.
[0063] The embodiments disclosed herein should be considered in all respects to be illustrative and not restrictive. The scope of the present invention is not limited to the embodiments disclosed herein, but is indicated by the claims, and all modifications within the meaning and scope equivalent to the claims are intended to be included. (1) Unlike the above examples, Ge, Te, etc. may be used as n-type impurities. (2) Unlike the above embodiment, crystal growth may be carried out using other substrates such as a sapphire substrate. (3) Unlike the above examples, the GaN cap layer may contain elements other than GaN. (4) The temperature at which crystal growth occurs in the second layer lamination process and the temperature at which crystal growth occurs in the third layer lamination process are not limited to the temperatures disclosed in the above embodiments. Furthermore, the temperature at which crystal growth occurs in the second layer lamination process may be the same as the temperature at which crystal growth occurs in the third layer lamination process. In other words, the temperature at which crystal growth occurs in the second layer lamination process is sufficient as long as it is higher than or equal to the temperature at which crystal growth occurs in the third layer lamination process. (5) Unlike the above embodiment, the first n-GaN layer (third layer) may contain AlN at a lower mole fraction than the n-AlInN layer (first layer). In other words, the third layer is laminated on the surface of the n-AlGaN composition gradient layer (second layer), and is a layer in which the mole fraction of AlN is smaller than that of the first layer and which contains Ga in its composition. [Explanation of Symbols]
[0064] 1…Nitride semiconductor light-emitting element 12...n-AlInN layer (1st layer) 13…GaN cap layer (cap layer) 14...n-AlGaN composition gradient layer (second layer) 15...1st n-GaN layer (3rd layer)
Claims
1. A first layer containing Al and In in its composition; a cap layer including Ga as a composition and laminated on a surface of the first layer; a second layer including Al and Ga in its composition, the second layer being laminated on a surface of the cap layer; Equipped with A nitride semiconductor light emitting device, wherein a mole fraction of AlN at an interface of the second layer laminated on the surface of the cap layer is 0.36 or more and 0.44 or less.
2. a third layer laminated on a surface of the second layer, the third layer having a mole fraction of AlN smaller than that of the first layer and including Ga in its composition; 2 . The nitride semiconductor light emitting device according to claim 1 , wherein the mole fraction of AlN in the second layer has a composition gradient that gradually decreases toward the interface with the third layer.
3. 3. The nitride semiconductor light emitting device according to claim 1, wherein the cap layer has a thickness in a stacking direction that is greater than 0 and is equal to or smaller than 1 nm.
4. 3. The nitride semiconductor light emitting device according to claim 1, wherein the second layer has a thickness in a stacking direction of 4 nm or more and 15 nm or less.
5. A nitride semiconductor light-emitting element as described in claim 1 or claim 2, wherein the first layer, the cap layer, and the second layer are nitride semiconductors.
6. The nitride semiconductor light-emitting element described in claim 5, wherein the cap layer is made of Ga and N.
7. A method for manufacturing a nitride semiconductor light-emitting device using metal-organic chemical vapor deposition, comprising the steps of: a first layer lamination step of growing a first layer containing Al and In as a composition; a cap layer lamination step of growing a cap layer containing Ga as a composition on a surface of the first layer after the first layer lamination step; a second layer lamination step of growing a second layer containing Al and Ga as a composition on the surface of the cap layer after the cap layer lamination step is performed; a third layer lamination step of growing a third layer containing Ga as a composition on a surface of the second layer after the second layer lamination step is performed; Equipped with A method for manufacturing a nitride semiconductor light-emitting device, wherein a temperature for growing crystals of the second layer in the second layer stacking step is equal to or higher than a temperature for growing crystals of the third layer in the third layer stacking step.
8. The method for manufacturing a nitride semiconductor light-emitting element as described in claim 7, wherein the first layer, the cap layer, and the second layer are nitride semiconductors.
9. The method for manufacturing a nitride semiconductor light-emitting element described in claim 8, wherein the cap layer is made of Ga and N.